2012
DOI: 10.1134/s1021443712040073
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 24-epibrassinolide on in vitro micropropagation of highbush blueberry

Abstract: In order to elucidate effects of 24 epibrassinolide (EB) on the efficiency of in vitro regeneration of highbush blueberry (Vaccinium corymbosum L., cv. Brigitta blue), we analyzed variability of seven biopro ductive parameters in regenerant plants cultured on nutrient media differing in hormonal composition. The additive action of EB, cytokinin (2iP), and auxin (IAA) was discovered for several parameters, such as repro duction coefficient, weight of regenerant plants, and the content of anthocyanin pigments. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…Moreover, it was used to control hyperhydricity in in vitro carnation cultures (Lukatkin et al, 2017). 24-EpiB inhibited PLB formation in another hybrid Cymbidium cultivar (Teixeira da Silva, 2013b) but enhanced growth (improved rooting) in highbush blueberry (Kudryashova et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was used to control hyperhydricity in in vitro carnation cultures (Lukatkin et al, 2017). 24-EpiB inhibited PLB formation in another hybrid Cymbidium cultivar (Teixeira da Silva, 2013b) but enhanced growth (improved rooting) in highbush blueberry (Kudryashova et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Виявилося, що додавання до складу живильного середовища препаратів цитедоф та дропп із цитокініновою активністю стимулює процес утворення адвентивних бруньок, формування мікростебел та збільшує коефіцієнт розмноження у бересклета карликового, діоскореї кавказьської та кірказона маньчжурського [3]. Інша модифікація полягала в тому, що за знижених норм використання ауксинів та цитокінінів до живильного МС-середовища у культурі in vitro додавали 0,25 мг/л епібрасиноліду для регенерації Vaccinium corymbosum [12].…”
unclassified
“…Research on highbush blueberry micropropagation was started in the 1980s (Reed and Abdelnour-Esquivel, 1991) and then broadened and accelerated in recent years to improve the existing micropropagation protocols (Gao et al, 2018;Hung et al, 2016;Kudryashova et al, 2012;Ru zi c et al, 2012). In the beginning, research was focused on finding the optimal culture media for micropropagation and checking the influence of diverse growth regulators (Chandler and Draper, 1986;Da Silva et al, 2006;Eccher and Noe, 1989;Eccher et al, 1986;Gajdo sov a et al, 2006;Isutsa et al, 1994;Ostroluck a et al, 2002Ostroluck a et al, , 2004Reed and Abdelnour-Esquivel, 1991;Tetsumura et al, 2008;Zhang et al, 2006).…”
mentioning
confidence: 99%
“…The results showed that the most suitable medium for this species was McCown's Woody Plant Basal Salt Mixture, or Woody Plant Medium (WPM), as described by Lloyd and McCown (1980). In the following years, the influence of different plant hormones on the efficiency of in vitro regeneration of highbush blueberry was studied (Kudryashova et al, 2012), and other investigations also were made on the antioxidant and anti-inflammatory properties of V. corymbosum L. (Samad et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation